A Review of Image Segmentation Methodologies in Medical Image - Lee, Lay Khoon; Liew, Siau-Chuin; Thong, Weng Jie (Springer, 2015)
A precise segmentation of medical image is an important stage in contouring throughout radiotherapy preparation. Medical images are mostly used as radiographic techniques in diagnosis, clinical studies and treatment planning. This review paper defines the limitation and strength of each methods currently existing for the segmentation of medical images.